2013
DOI: 10.1371/journal.pone.0081570
|View full text |Cite
|
Sign up to set email alerts
|

High Connectivity of Animal Populations in Deep-Sea Hydrothermal Vent Fields in the Central Indian Ridge Relevant to Its Geological Setting

Abstract: Dispersal ability plays a key role in the maintenance of species in spatially and temporally discrete niches of deep-sea hydrothermal vent environments. On the basis of population genetic analyses in the eastern Pacific vent fields, dispersal of animals in the mid-oceanic ridge systems generally appears to be constrained by geographical barriers such as trenches, transform faults, and microplates. Four hydrothermal vent fields (the Kairei and Edmond fields near the Rodriguez Triple Junction, and the Dodo and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 47 publications
4
39
0
1
Order By: Relevance
“…Its distribution varies from location to location, although it is most abundant in the Kairei and Solitaire fields, and least abundant in the DoDo field. No significant differences were detected in genetic diversity between the Solitaire and Kairei populations (Beedessee et al 2013), which is consistent with the results of a previous study that found a 0.2 % difference in genetic diversity between Austinograea populations in the Kairei and Edmond fields (Van Dover et al 2001). Congeneric species are found in the western Pacific vent fields, whereas crabs of different genera are found in the eastern Pacific and MAR vent fields (summarized in Desbruyères et al 2006).…”
Section: Distribution and Connectivity Of Vent Faunasupporting
confidence: 91%
See 2 more Smart Citations
“…Its distribution varies from location to location, although it is most abundant in the Kairei and Solitaire fields, and least abundant in the DoDo field. No significant differences were detected in genetic diversity between the Solitaire and Kairei populations (Beedessee et al 2013), which is consistent with the results of a previous study that found a 0.2 % difference in genetic diversity between Austinograea populations in the Kairei and Edmond fields (Van Dover et al 2001). Congeneric species are found in the western Pacific vent fields, whereas crabs of different genera are found in the eastern Pacific and MAR vent fields (summarized in Desbruyères et al 2006).…”
Section: Distribution and Connectivity Of Vent Faunasupporting
confidence: 91%
“…No genetic differentiation exists between R. kairei populations in the Kairei and Edmond fields (Van Dover et al 2001). Recently, population genetic analysis of R. kairei was undertaken using a partial mitochondrial cytochrome oxidase c subunit I (COI) sequence, of the three vent populations on the CIR; again, no genetic differences were detected (Beedessee et al 2013). The congeneric species R. exoculata and R. hybisae are found on both the MAR and the Mid-Cayman Rise (MCR) (Nye et al 2012).…”
Section: Distribution and Connectivity Of Vent Faunamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Young et al (2008) found a general southward pattern of migration along the northeast Pacific system, and larger effective population sizes of the siboglinid tubeworm Ridgeia piscesae in the southern populations compared to those in the north. Coalescent approaches have also been implemented to measure long-term migration rates in mollusk and polychaete species along the EPR (Plouviez et al, 2009(Plouviez et al, , 2010(Plouviez et al, , 2013, crustacean and mollusk species in the Indian Ocean ridges (Thaler et al, 2011;Beedessee et al, 2013;Chen et al, 2015), alvinocaridid shrimp from the MidCayman Spreading Center (Plouviez et al, 2015) and the Mid-Atlantic Ridge (Teixeira et al, 2012(Teixeira et al, , 2013. Despite the evident advantages of coalescent approaches over traditional Fstatistics, the migration estimates obtained through many of these approaches are considered long-term because of necessary equilibrium assumptions over the last ∼4N e generations (i.e., average time to coalescence).…”
Section: Genetic Approaches To Metacommunity Dynamics On Ecological Tmentioning
confidence: 99%
“…This study is the first to investigate population genetics of vent shrimps in the Northwest Pacific, facilitating comparison with the observed patterns on the MidAtlantic Ridge (MAR; Teixeira et al 2011Teixeira et al , 2012, Central Indian Ridge (CIR; Beedessee et al 2013), and in the southwestern Pacific (SWP; Thaler et al 2014).…”
Section: Introductionmentioning
confidence: 99%